KEPENTINGAN PEMERINTAH DAERAH DALAM PENCAPAIAN SWASEMBADA BERAS DI KABUPATEN SIAK TAHUN 2012 - Putri, Gusnatika; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to describe the implementation of food security programs in addressing the problem of shortage of food needs such as rice Researchers use a political approach to food is to know the actors directly involved in the rice self-sufficiency program and its importance, determine the presence of rice self-sufficiency goal, know what factors affect the achievement of self-sufficiency in rice and facilities whether it has been adequately done in implementing the program of the local government in order to achieve self-sufficiency in rice in Siak in 2012. The theory that I use is the theory Merilee S Grindle which states that the success of policy implementation is influenced by two variables, namely the policy content and the implementation environment.The method used in this study is qualitative methods of data that can not be expressed in terms of numbers but in the form of an explanation that describes the shape of the state, a process, a particular event.The results showed that the implementation of the food security program in achieving rice swasemabada has not reached the desired target. This is due to the actors involved in the implementation of the program do not understand the purpose in carrying out policies that have been made, as the goal of increasing the planting area through land use and improve the quality of human resources in support of the implementation of the program so that the many obstacles that can not be resolved by the actors.Besides the political, social and economic influence also in the implementation of food security programs in achieving self-sufficiency rice in the regency of siak in 2012.Keywords: food security, policy implementation, and interests.